Implementation of the Rapid Application Development Method for Designing an Outpatient Online Registration System in an Independent Doctor's Practice - Nurhayati Nurhayati; Muhammad Amin bin Sahari; Tominanto Tominanto; Danang Yudha Laksono (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
The use of the website has become a necessity in health services and makes it easier to work in health care facilities. Doctors' independent practice as a health service facility can use the website to assist the outpatient registration process. Outpatient registration services at independent doctor's practices still use a manual system, patients must come to registration, take a queue card printed by the officer, wait according to the queue number obtained so that the process causes patient waiting time at the service to be long. The purpose of this study is to produce an outpatient online registration system in independent doctor’s practices that is able to assist outpatients to register online for outpatients. Development of an Outpatient Online Registration System at this Independent Doctor's Practice using the Rapid Application Development (RAD) method, this development model is used because this model is considered a time-honored model, so the process is relatively faster. This study applies the Rapid Application Development method to produce an outpatient online registration system at independent Practitioners that is able to manage patient data, doctor data, polyclinic queue data, polyclinic data, queue data and outpatient registration data. The Rapid Application Development method has been able to streamline the processing time for making the system to produce an Outpatient Online Registration System.